Implementasi Standar Operasional Prosedur Alur Produksi - Putri, Zahra Qanitah Ferdyan; Chaniago, Harmon; Mukaram, Mukaram; Raharso, Sri; Tiorida, Ermina; Sutisna, Ma’mun; Efawati, Yen (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2024)
Companies use various methods to create efficiency in production. One of them is creating and implementing Standard Operating Procedures (SOP) for production flow. This is done to adapt to technological developments and changes in consumer tastes. Based on the results of observations and discussions with partner companies engaged in the fashion sector, information was obtained that they needed a production flow SOP. On this basis, a production flow SOP was created. There are eight work steps in making it, starting from identifying the goals and objectives of the SOP, collecting information, collecting the SOP format, determining the SOP format to be created, writing the SOP, reviewing and revising, testing and finalizing. Based on work steps in making and using existing equipment, a production flow SOP was produced. The survey results prove that the implementation of the SOP has an impact on increasing efficiency in production and increasing consumer satisfaction.